The role of single nucleotide polymorphisms related to iron homeostasis in mesothelioma susceptibility after asbestos exposure: a genetic study on autoptic samples - Grignani, Pierangela; Visonà, Silvia Damiana; Fronda, Maria Vittoria; Borrelli, Paola; Monti, Maria Cristina; Bertoglio, Barbara; Conti, Adelaide; Fattorini, Paolo; Previderè, Carlo (Frontiers in Public Health, 2023)
Asbestos-related diseases still represent a major public health problem all over the world. Among them, malignant mesothelioma (MM) is a poor-prognosis cancer, arising from the serosal lining of the pleura, pericardium and peritoneum, triggered by asbestos exposure. Literature data suggest the key role of iron metabolism in the coating process leading to the formation of asbestos bodies, considered to be both protective and harmful. Two sample sets of individuals were taken into consideration, both residing in Broni or neighboring cities (Northwestern Italy) where an asbestos cement factory was active between 1932 and 1993. The present study aims to compare the frequency of six SNPs involved in iron trafficking, previously found to be related to protection/predisposition to MM after asbestos exposure, between 48 male subjects with documented asbestos exposure who died of MM and 48 male subjects who were exposed to asbestos but did not develop MM or other neoplastic respiratory diseases (Non-Mesothelioma Asbestos Exposed – NMAE). The same analysis was performed on 76 healthy male controls. The allelic and genotypic frequencies of a sub-group of 107 healthy Italian individuals contained in the 1000 genomes database were considered for comparison. PCR-multiplex amplification followed by SNaPshot mini-sequencing reaction was used. The findings presented in this study show that the allelic and genotypic frequencies for six SNP markers involved in iron metabolism/homeostasis and the modulation of tumor microenvironment are not significantly different between the two sample sets of MM and NMAE. Therefore, the SNPs here considered do not seem to be useful markers for individual susceptibility to mesothelioma. This finding is not in agreement with previous literature.